The perfect marriage - Rose, Jeneva ([Place of publication not identified] : Bloodhound Books, 2020)
A high-powered attorney finds herself defending her much less successful husband after his mistress is found stabbed in the married couple's second home.
On cover, the word "perfect" is struck-out such that the title may be read as "The marriage."
Keywords: Women lawyers -- Fiction; Marital conflict -- Fiction; Adultery -- Fiction; Mistresses -- Crimes against -- Fiction; Murder -- Investigation -- Fiction; Psychological fiction; Thrillers (Fiction)